An Overview of the Need for Circular Economy on Electric Vehicle Batteries - S. Padmanabhan, C. Joel, S. Mahalingam, J. R. Deepak, T. Vinod Kumar and Deborah Raj (Nature Environment and Pollution Technology, 2024)
Batteries are a widely utilized and simple method for powering electronic devices, particularly given the prevalence of individuals traveling to all gadgets. The escalating adoption of electric vehicles and portable electronic devices has led to a surge in the demand for lithium-ion batteries. Consequently, this has given rise to supply uncertainties in acquiring essential minerals such as lithium and cobalt, along with concerns about the proper disposal of dead batteries. The existing methods for battery recycling exhibit variations based on the individual chemistries of the batteries, hence influencing both cost factors and greenhouse gas emissions. Simultaneously, there exists a possibility for repurposing depleted batteries for low-tier energy storage applications. The absence of legislation pertaining to the secure storage and handling of waste streams contributes to the accumulation of refuse in exposed environments and the release of hazardous substances from landfills. In addition, contemporary battery manufacturing methods necessitate the utilization of innovative substances, such as ionic liquids for electrolytes and nanostructures for cathodes, to enhance the energy characteristics and longevity of batteries. The presence of uncertainties regarding the accurate assessment of the environmental consequences associated with novel battery chemicals has the potential to impede efforts aimed at recycling and containment. The objective of this analysis is to consolidate the existing knowledge regarding battery pollutants, both those that are recognized and those that remain uncertain, and to assess their potential environmental impacts. Additionally, this research aims to examine the current strategies and methods employed for the recycling of batteries in the circular economy.